Dose rate versus gantry speed test in RapidArc commissioning: a feasibility study using ArcCHECK. (16th December 2016) - Yang, B; Geng, H; Kong, C W; Lam, W W; Cheung, K Y; Yu, S K
Abstract: The present study was to investigate the feasibility of using ArcCHECK for dose rate versus gantry speed test in RapidArc commissioning. Current test methods using film or electronic portal imaging device could not provide information about dose rate, gantry speed and actual gantry angle at each control point. The technique proposed aimed to directly measure those parameter variations during plan delivery. The device was isocentrically set up and programmed to record the detector signal and gantry angle every 50 ms as a movie file. A plan with variable gantry speed ranging from 1° s –1 to 6° s –1 was designed for testing the accuracy of measured gantry speed without dose rate modulation. A dose rate versus gantry speed test was designed for testing some extreme machine settings. The processed data of gantry angle had a mean deviation of 0.01° from the machine log data. Linear regression was applied to the processed angle versus time data to obtain an averaged gantry speed between control points. The uncertainty of calculated gantry speed was found to be within 1% for plans with or without dose rate modulation. The mean deviation of measured dose rate was 0.01%, with range of −0.58% to 0.56%. The deviation of characteristic parameter MU/degree for the dose rate versus gantry speed plan ranged from −0.70% to 0.60%. The actual gantry angle at each control point was calculated to have a difference within 0.5° when compared with the plan setting. Our proposed method can measure the dose rate, gantry speed and actual gantry angle at each control point directly and accurately.